Parametric Mapping Cardiac Magnetic Resonance Imaging for the Diagnosis of Myocarditis in Children in the Era of COVID-19 and MIS-C - Bibhuti B. Das; Jyothsna Akam-Venkata; Mubeena Abdulkarim; Tarique Hussain (MDPI AG, 2022)
Myocarditis comprises many clinical presentations ranging from asymptomatic to sudden cardiac death. The history, physical examination, cardiac biomarkers, inflammatory markers, and electrocardiogram are usually helpful in the initial assessment of suspected acute myocarditis. Echocardiography is the primary tool to detect ventricular wall motion abnormalities, pericardial effusion, valvular regurgitation, and impaired function. The advancement of cardiac magnetic resonance (CMR) imaging has been helpful in clinical practice for diagnosing myocarditis. A recent Scientific Statement by the American Heart Association suggested CMR as a confirmatory test to diagnose acute myocarditis in children. However, standard CMR parametric mapping parameters for diagnosing myocarditis are unavailable in pediatric patients for consistency and reliability in the interpretation. The present review highlights the unmet clinical needs for standard CMR parametric criteria for diagnosing acute and chronic myocarditis in children and differentiating dilated chronic myocarditis phenotype from idiopathic dilated cardiomyopathy. Of particular relevance to today's practice, we also assess the potential and limitations of CMR to diagnose acute myocarditis in children exposed to severe acute respiratory syndrome coronavirus-2 infections. The latter section will discuss the multi-inflammatory syndrome in children (MIS-C) and mRNA coronavirus disease 19 vaccine-associated myocarditis.